2016
DOI: 10.1108/ijm-12-2014-0263
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, wages and profits among Belgian firms: do fixed-term contracts matter?

Abstract: Purpose – The purpose of this paper is to estimate the impact of fixed-term contracts (FTCs) on labour productivity, wages (i.e. labour cost), and productivity-wage gaps (i.e. profits). Design/methodology/approach – The authors apply dynamic panel data techniques to detailed Belgian linked employer-employee panel data covering the period 1999-2006. Findings – Results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
1
10
0
1
Order By: Relevance
“…After implementation of labour force reduction, activities such as layoffs and delayering employees' output is increased as they battle to attain and retain management and director's attention so they can avoid getting laid off or get positions of prominence after delayering exercises (Pearce and Robinson, 2015). This is also supported by Garnero et al (2016) who pointed out that some employees go to lengths of requesting for additional tasks from management or supervisors in attempts to prove their value in the organisation. This creates a competitive environment which rubs off fellow employees improve output per employee notably (De Meuse and Dai, 2013;Oke and Kach, 2012;Tomprou et al, 2015;Zohrabi, 2013).…”
Section: Production Timementioning
confidence: 77%
See 1 more Smart Citation
“…After implementation of labour force reduction, activities such as layoffs and delayering employees' output is increased as they battle to attain and retain management and director's attention so they can avoid getting laid off or get positions of prominence after delayering exercises (Pearce and Robinson, 2015). This is also supported by Garnero et al (2016) who pointed out that some employees go to lengths of requesting for additional tasks from management or supervisors in attempts to prove their value in the organisation. This creates a competitive environment which rubs off fellow employees improve output per employee notably (De Meuse and Dai, 2013;Oke and Kach, 2012;Tomprou et al, 2015;Zohrabi, 2013).…”
Section: Production Timementioning
confidence: 77%
“…In an empirical study investigated by Kavadis and Castaner (2015) results showed that in times of poor performance, organisations that employed restructuring as a labour cost reduction method improved the performance of their organisations mitigating the inefficient bottle necks of tall organisational structures and redundant skills within an organisation. Garnero et al (2016) emphasized that organisations' on and off employment techniques have a strong positive relationship on the production efficiency of an organisation, Conversely, Goesaert et al (2015) found that organisations that reduced their labour cost with the intent of increasing production efficiency experienced great declines in production efficiency with production taking longer than it did prior to downsizing. While organisations that cut labour costs due to economic hardship only faced a disdaining drop in productive efficiency during the labour cost reduction exercises.…”
Section: Production Timementioning
confidence: 99%
“…While a number of researchers argue that various benefits can accrue to employees in non-standard positions, such as better reconciliation of work and life and higher control over work schedules, it is shown that the positive effects are highly dependent on the context and atypical jobs, on average, have lower pay and less security (Booth et al, 2002;Gash and McGinnity, 2007;Cazes and de Laiglesia, 2015). Across a number of countries, large and persistent wage gaps exists between different types of contract holders (Duman, 2019;Garnero et al, 2016). Moreover, employees in precarious positions are subject to lower protection by labor legislation and union membership because of higher turnover and lack of integration of such workers into the collective bodies (Vosko et al, 2009;Grimshaw, 2011).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…However, policy makers began to be aware of the connection between wage stagnation and inequality due to consequences for the society. Garnero et al (2016) investigated the impact of fi xed-term contracts (FTCs) on labor productivity, wages (i.e. labor cost) and productivity wage gaps (i.e.…”
Section: Empirical Analysis: Empirical Literature Overviewmentioning
confidence: 99%